Preparation method of high-load supercapacitor electrode and supercapacitor composite electrode

By using Bassa wood as a biocarbon material, combining carbon nanotubes and CeO2 to form CeO2/BWC-CNTs composite electrodes, the reduction of capacitance and increase of binder caused by volume changes in metal oxide nanostructures during charging and discharging is solved. Cost and pollution problems achieve high specific capacitance and long life supercapacitor electrodes.

CN119400610APending Publication Date: 2025-02-07ZHEJIANG UNIV OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411784115.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The metal oxide nanostructures of existing supercapacitor electrodes vary greatly during charging and discharging, resulting in crushing and peeling, reducing capacitance and service life, and traditional electrodes require the addition of adhesive to increase costs and environmental pollution.

Method used

Bassa wood is used as a biocarbon material to grow carbon nanotubes by cutting, stabilizing, carbonizing, activation and chemical vapor deposition. Combining Ce-MOF derivative CeO2, CeO2, to form CeO2/BWC-CNTs composite electrodes, avoiding the use of binders .

Benefits of technology

Improves the specific capacitance and electrochemical stability of the electrode, reduces production costs and environmental pollution, and achieves high load and long life supercapacitor electrodes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119400610A_ABST
    Figure CN119400610A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of energy storage, and provides a preparation method of a high-load supercapacitor electrode, which comprises the following steps: cutting balsa wood as a raw material along the longitudinal growth direction through the steps S1-S8, stabilizing balsa wood chips, and carbonizing to obtain porous carbon used as a self-supporting framework. The method comprises the following steps: taking BWC-CNTs as a raw material, activating the BWC-CNTs in an activating agent to obtain a hydrophilic surface and a large specific surface area, soaking hydrophilic porous carbon in a Ni (NO3) 2 solution to introduce a Ni catalyst, taking a ferrocene xylene solution as a precursor, growing CNTs on the porous carbon by adopting a chemical vapor deposition method, and finally sintering at high temperature to obtain the CeO2 / BWC-CNTs electrode. The invention further discloses a super capacitor composite electrode, a larger surface area is provided to increase capacitance, the self-growth characteristic of the electrode is adopted, so that no binder needs to be added into the electrode, the production cost is low, the cost increase and environmental pollution caused by the use of an organic binder are avoided, and the excellent conductivity of the electrode is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of energy storage technology, and in particular to a method for preparing a high-load supercapacitor electrode and a supercapacitor composite electrode. Background Art

[0002] Supercapacitors are a new type of energy storage device with high power density, long cycle life and fast charge and discharge characteristics. The key to their performance lies in the preparation of electrode materials. Due to their high power density, fast charge and discharge and excellent electrochemical properties, they are one of the most popular electrochemical energy storage devices in portable electronic devices, electric vehicles and stationary energy storage facilities. As a key component of supercapacitors, electrodes are made of a variety of materials, such as carbon materials, transition metal oxides / hydroxides / sulfides / selenides / phosphates, MXenes, conductive polymers, etc.

[0003] EP4229664B1 discloses a method for directly growing cross-linked carbon nanotubes on a microstructured metal substrate for supercapacitor applications. A method for manufacturing an electrode for a supercapacitor, the method comprising the following process steps: etching a microstructure with a predetermined roughness in the surface of a metal film substrate, depositing a metal or metal compound layer in the microstructure, converting the metal or compound layer into metal nanoparticles to constitute a catalyst, and growing cross-linked carbon nanotubes in the microstructure at the metal nanoparticles as a catalyst.

[0004] CN118824747A discloses a method for preparing a cylindrical supercapacitor electrode, comprising the following steps: a) dissolving carboxymethyl cellulose in deionized water; b) mixing conductive carbon and activated carbon after completely removing water; c) adding the mixed carbon material to the prepared carboxymethyl cellulose solution and stirring and mixing with a double planetary stirrer; d) adding the polyacrylate dispersion to the prepared slurry and stirring and mixing with a double planetary stirrer; e) adjusting the pH value of the prepared slurry; f) adding polytetrafluoroethylene emulsion to the prepared slurry and stirring and mixing with a double planetary stirrer; g) adding polyvinyl pyrrolidone and propylene carbonate to the slurry and stirring and mixing with a double planetary stirrer; h) treating the prepared slurry through a colloid mill device, filtering after treatment, and removing bubbles under a vacuum environment; i) using the prepared material to prepare electrodes, assemble devices, and test the high-temperature load performance of the devices.

[0005] CN118545713A discloses a method for preparing a wood asphalt-based porous carbon material and its application in 3D printed supercapacitors. The method comprises the following steps: 1) preparing oxidized wood asphalt: pre-treating the wood asphalt by ball milling, adding hydrogen peroxide and ultrasonically mixing, then heating in a water bath for reaction, then washing, filtering and drying to obtain oxidized wood asphalt; 2) preparing rosin-wood asphalt-based porous carbon material: grinding and mixing the oxidized wood asphalt obtained in step 1) with chitosan and acrylic rosin, then pre-carbonizing under nitrogen protection, then grinding and mixing the obtained product with KOH, and activating under nitrogen protection, and acid-washing, washing with water and drying the activated product to obtain a rosin-wood asphalt-based porous carbon material.

[0006] Carbon-based electrodes have good cycling performance, which originates from the mechanism of electronic double layer capacitance (EDLC). Since most commercial carbon electrodes are made from fossil fuel precursors such as petroleum coke and coal, they are expensive and non-renewable. Carbon can also be obtained from biomass carbonization, which has multiple advantages in addition to its ideal porous structure, including natural abundance, eco-friendly renewability, diverse options, and cost-effectiveness. Various renewable biomasses, such as wood residues, tea waste, coconut fiber, and palm bark, have been converted into activated carbon and used as electrodes for supercapacitors. Typically, biomass carbon materials are ground into powders and then mixed with a binder to form a paste for coating on current collectors. However, this preparation process destroys the hierarchical structure of biomass and introduces non-conductive polymers, which will inevitably increase the charge transfer resistance. Compared with carbon powder, the carbon sheet with the original biostructure has more ion transmission channels and electron conduction paths. More importantly, it can be used directly as an electrode without the need for binders or conductive additives.

[0007] In order to further improve the electrochemical performance of biomass conversion carbon electrodes, the obtained porous carbon can be coupled with various metal oxides / sulfides to increase the surface-to-volume ratio and provide additional pseudocapacitance. In the prior art, MnFe2O4 hollow spheres and NiS needles are fixed on biomass porous carbon. Due to the synergistic effect between MnFe2O4 and NiS, the hybrid electrode exhibits an ultra-high specific capacitance of 640F / g. However, the metal oxide nanostructure undergoes a large volume change during charging and discharging, causing it to shatter and peel off from the carbon substrate, resulting in a significant reduction in capacitance and service life. Summary of the invention

[0008] Long-term practice has found that the metal oxide nanostructures in the existing technology undergo large volume changes during the charging and discharging process, causing them to shatter and peel off from the carbon substrate, resulting in a significant reduction in capacitance and service life, that is, the specific capacitance of the supercapacitor electrode decays with the increase in the number of charge and discharge cycles. Traditional capacitor electrodes have low space utilization and low specific surface area. Binders need to be added during the electrode production process, and the use of organic binders causes technical problems such as increased costs and environmental pollution.

[0009] In view of this, the present invention aims to provide a method for preparing a high-load supercapacitor electrode, comprising:

[0010] Step S1, cutting the balsa wood along the longitudinal direction of the tree growth to obtain balsa wood chips with a thickness of d;

[0011] Step S2, subjecting the balsa wood chips to a stabilization treatment process, and then to a carbonization treatment, followed by sandpaper polishing, cleaning and drying to obtain balsa wood carbon chips;

[0012] Step S3, soaking the balsa wood carbon sheet in an aqueous solution containing an activator, and then activating, washing and drying to obtain a first material;

[0013] Step S4, immersing the first material in a Ni(NO3)2 solution to introduce a Ni catalyst, and freeze-drying the ferrocene-xylene solution as a precursor to obtain a second material;

[0014] Step S5, in-situ growing carbon nanotubes on the second material by chemical vapor deposition to obtain a third material;

[0015] Step S6, immersing the third material in an aqueous solution of cerium ammonium nitrate, heating the temperature to T1, cooling to T2, rinsing with deionized water, repeating 3 to 10 times, and drying to obtain a fourth material;

[0016] Step S7, adding an aqueous solution of ammonium cerium nitrate and trimesic acid to an organic solvent to form a uniform solution; soaking the fourth material in the uniform solution, and placing it in a high-pressure reactor at a temperature of T3 and maintaining it for a time of t1 to obtain a fifth material;

[0017] Step S8, washing the fifth material with deionized water, placing it in an oven to dry, and placing the dried material in a tubular furnace to sinter, thereby obtaining CeO2 / BWC-CNTs.

[0018] In one embodiment, in step S2, the stabilization process includes heat preservation treatment in air or argon protection, the heat preservation temperature is 200°C-300°C, and the heat preservation time is 4h-8h.

[0019] In one embodiment, in step S2, the carbonization treatment is performed by carbonizing in an inert gas, the inert gas includes argon, the carbonization temperature is 900° C.-1150° C., and the carbonization time is 4 h-12 h.

[0020] In one embodiment, in step S2, the drying temperature is 110°C-120°C, and the drying time is 3h-5h.

[0021] In one embodiment, the activating agent selected during the activation process includes KOH or NaOH or Na2CO3 or MgCl2 or ZnCl2 or H3PO4.

[0022] In one embodiment, the concentration of the activator aqueous solution during the activation process is 1-6 mol / L.

[0023] In one embodiment, in step S7, the organic solvent is N,N-dimethylformamide, the concentration of the aqueous solution of cerium ammonium nitrate is 0.4 mol / L-0.6 mol / L, the mass of trimesic acid is 0.8-1.2 g, the temperature T3 is 20°C-90°C, and the holding time t1 is 6h-24h.

[0024] In one embodiment, step S5 includes step S51, evaporating the carbon source at 30° C.-80° C. and bringing the carbon source into a reaction zone of an activated carbon sheet loaded with a Ni catalyst on the second material by gas to grow carbon nanotubes.

[0025] In one embodiment, the carbon source is a xylene solution in which an auxiliary catalyst ferrocene is dissolved, and the concentration of ferrocene in the xylene solution is 0.01 g / mL-0.1 g / mL.

[0026] In one embodiment, in step S8, the firing temperature in the tube furnace is 700° C.-900° C., and the firing time is 1 h-6 h.

[0027] The present invention also discloses a supercapacitor composite electrode. The supercapacitor composite electrode is prepared by the above-mentioned preparation method of the high-load supercapacitor electrode. The supercapacitor composite electrode comprises CeO2 / BWC-CNTs.

[0028] The preparation method of the high-load supercapacitor electrode disclosed in the present invention, through steps S1-S8, cut balsa wood along the longitudinal direction of growth as raw material, stabilize the balsa wood slices and then perform carbonization treatment to obtain porous carbon as a self-supporting frame. After activation in an activator, a hydrophilic surface and a large specific surface area are obtained, and the hydrophilic porous carbon is soaked in a Ni(NO3)2 solution to introduce a Ni catalyst, and freeze-dried to obtain a second material. CNTs are grown on porous carbon using a typical chemical vapor deposition method to obtain BWC-CNTs, allowing Ce ions to fully enter the pores of BWC-CNTs, and a certain concentration of cerium ammonium nitrate aqueous solution is configured. The BWC-CNTs are soaked at a certain temperature, and rinsed with deionized water after cooling. Repeated drying multiple times to obtain a fourth material, the fourth material is WRBWC-CNTs. Ce-MOF is grown on WRBWC-CNTs porous carbon by a hydrothermal method to obtain a fifth material, the fifth material is Ce-MOF / BWC-CNTs. The CeO2 / BWC-CNTs electrode is obtained by high-temperature sintering. The present invention also discloses a supercapacitor composite electrode. The present invention selects balsa wood as the source of biocarbon material, which is low in cost. By adding high-density carbon nanotubes, the specific surface area of ​​biomass carbon converted from balsa wood is increased, providing more surface area to increase capacitance, providing more active iron and nickel sites to participate in reduction and oxidation reactions, thereby increasing the capacitance of the electrode, from 52.9m 2 g 2 Increased to 71.4m 2 g 2 The CeO2 derivative of Ce-MOF was introduced to form a composite electrode CeO2 / BWC-CNTs. 2 At a current density of 10000mF / cm 2 After 10,000 charge and discharge cycles, the capacitance of the electrode still remains at 100.5%, further increasing the specific capacitance of the electrode. The self-growth characteristics of the electrode make it unnecessary to add any binder to the electrode, which has low production costs and avoids the cost increase and environmental pollution caused by the use of organic binders, while ensuring the excellent conductivity of the electrode. It not only improves the quality and performance of the composite material, but also complies with the principles of green chemistry, saves resources and protects the environment.

[0029] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The schematic embodiments of the present invention and the description thereof are used to explain the present invention and do not constitute improper limitations on the present invention.

[0031] In the attached picture:

[0032] Figure 1 A schematic diagram of a method for preparing a high-load supercapacitor electrode according to an embodiment of the present invention;

[0033] Figure 2 is a SEM image of a balsa wood carbon sheet (BWC) according to an embodiment of the present invention;

[0034] Figure 3 This is a high-magnification SEM image of a BWC-CNTs composite electrode according to an embodiment of the present invention;

[0035] Figure 4 This is a longitudinal cross-sectional SEM image of a CeO2 / BWC-CNTs composite electrode according to an embodiment of the present invention. DETAILED DESCRIPTION

[0036] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.

[0037] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0038] It should be noted that the terms "first", "second", "third", etc. in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so as to describe the embodiments of the present invention described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.

[0039] In order to solve the problem in the prior art that metal oxide nanostructures undergo large volume changes during charging and discharging, resulting in their crushing and peeling off from the carbon substrate, resulting in a significant reduction in capacitance and service life, that is, the specific capacitance of supercapacitor electrodes decays with the increase in the number of charge and discharge cycles. Traditional capacitor electrodes have low space utilization and low specific surface area. Binders need to be added during the electrode production process, and the use of organic binders causes technical problems such as increased costs and environmental pollution. The present invention provides a method for preparing high-load supercapacitor electrodes, such as Figure 1 As shown, a schematic diagram of a method for preparing a high-load supercapacitor electrode according to an embodiment of the present invention is provided. The method for preparing a high-load supercapacitor electrode comprises:

[0040] Step S1, cutting the balsa wood along the longitudinal direction of the tree growth to obtain balsa wood chips with a thickness of d;

[0041] Step S2, subjecting the balsa wood chips to a stabilization treatment process, and then to a carbonization treatment, followed by sandpaper polishing, cleaning and drying to obtain balsa wood carbon chips;

[0042] Step S3, soaking the balsa wood carbon sheet in an aqueous solution containing an activator, and then activating, washing and drying to obtain a first material;

[0043] Step S4, immersing the first material in a Ni(NO3)2 solution to introduce a Ni catalyst, and freeze-drying the ferrocene-xylene solution as a precursor to obtain a second material;

[0044] Step S5, in-situ growing carbon nanotubes on the second material by chemical vapor deposition to obtain a third material;

[0045] Step S6, immersing the third material in an aqueous solution of cerium ammonium nitrate, heating the temperature to T1, cooling to T2, rinsing with deionized water, repeating 3 to 10 times, and drying to obtain a fourth material;

[0046] Step S7, adding an aqueous solution of ammonium cerium nitrate and trimesic acid to an organic solvent to form a uniform solution; soaking the fourth material in the uniform solution, and placing it in a high-pressure reactor at a temperature of T3 and maintaining it for a time of t1 to obtain a fifth material;

[0047] Step S8, washing the fifth material with deionized water, placing it in an oven to dry, and placing the dried material in a tubular furnace to sinter, thereby obtaining CeO2 / BWC-CNTs.

[0048] The preparation method of the high-load supercapacitor electrode disclosed in the present invention comprises the following steps: cutting balsa wood along the longitudinal direction of growth as raw material, stabilizing the balsa wood slices and then carbonizing them to obtain porous carbon as a self-supporting frame. After activation in an activator, a hydrophilic surface and a large specific surface area are obtained, a Ni(NO3)2 solution is used to soak the hydrophilic porous carbon to introduce a Ni catalyst, a ferrocene-xylene solution is used as a precursor, and a typical chemical vapor deposition method is used to grow CNTs on the porous carbon to obtain BWC-CNTs. The third material is BWC-CNTs, allowing Ce ions to fully enter the pores of BWC-CNTs, configuring a certain concentration of cerium ammonium nitrate aqueous solution, soaking BWC-CNTs at a certain temperature, rinsing with deionized water after cooling, and repeatedly drying to obtain a fourth material, which is WRBWC-CNTs. Ce-MOF is grown on WRBWC-CNTs porous carbon by hydrothermal method to obtain the fifth material, which is Ce-MOF / BWC-CNTs. CeO2 / BWC-CNTs electrode is obtained by high temperature sintering. The present invention also discloses a supercapacitor composite electrode. The present invention selects balsa wood as the source of biocarbon material, which is low in cost. By adding high-density carbon nanotubes, the specific surface area of ​​biomass carbon converted from balsa wood is increased, providing more surface area to increase capacitance, providing more active iron and nickel sites to participate in reduction and oxidation reactions, thereby increasing the capacitance of the electrode, from 52.9m 2 g 2 Increased to 71.4m 2 g 2 The CeO2 derivative of Ce-MOF was introduced to form a composite electrode CeO2 / BWC-CNTs. 2 At a current density of 10000mF / cm 2 After 10,000 charge and discharge cycles, the capacitance of the electrode still remains at 100.5%, further increasing the specific capacitance of the electrode. The self-growth characteristics of the electrode make it unnecessary to add any binder to the electrode, which has low production costs and avoids the cost increase and environmental pollution caused by the use of organic binders, while ensuring the excellent conductivity of the electrode. It not only improves the quality and performance of the composite material, but also complies with the principles of green chemistry, saves resources and protects the environment.

[0049] In step S1, the balsa wood is cut along the longitudinal direction of the tree growth to obtain a uniform porous structure that does not pass through the annual rings, and a balsa wood chip with a thickness of d is obtained, and the thickness d of the balsa wood chip is 3-6 mm. More preferably, it is 3 mm, 4 mm, 5 mm or 6 mm. To further improve the surface quality and physical properties of the balsa wood carbon sheet, in step S2, sandpaper polishing, cleaning and drying are performed, and the sandpaper used for polishing is 3000 grit sandpaper. The reagent used for cleaning is deionized water or ethanol. The drying temperature is 110-120°C, and the drying time is 3-5h.

[0050] In order to chemically modify the balsa wood chips to improve their thermal stability and structural stability. Ensure that the moisture and volatile components in the wood are effectively removed while avoiding excessive damage to the wood structure. In a preferred embodiment of the present invention, in step S2, the stabilization process includes heat preservation treatment in air or argon protection, the heat preservation temperature is 200℃-300℃, and the heat preservation time is 4h-8h. More preferably, the heat preservation temperature is 200℃, 210℃, 220℃, 230℃, 240℃, 250℃, 260℃, 270℃, 280℃, 290℃ or 300℃.

[0051] Carbonization is usually a pyrolysis process carried out in an oxygen-deficient or low-oxygen environment to convert the stabilized balsa wood chips into carbon materials to obtain carbon materials with higher specific surface area and better conductivity. In a preferred embodiment of the present invention, in step S2, the carbonization process is carried out by carbonizing in an inert gas, the inert gas includes argon, the carbonization temperature is 900°C-1150°C, and the carbonization time is 4h-12h. More preferably, the carbonization process is carried out in nitrogen. The flow rate of the argon or nitrogen is 100-600sccm. The flow rate unit sccm is standard cubic centimeters per minute (StandardCubicCentimeters per Minute). More preferably, the flow rate is 100sccm, 200sccm, 300sccm, 400sccm, 500sccm or 600sccm. Maintaining an oxygen-deficient or inert atmosphere (such as nitrogen or argon) prevents oxidation of the material and ensures a higher carbon content and better conductivity.

[0052] In order to remove moisture and prevent hygroscopicity in subsequent use, in a preferred embodiment of the present invention, in step S2, the drying temperature is 110°C-120°C, and the drying time is 3h-5h.

[0053] The activation process is usually carried out at high temperature to form more pores, thereby increasing the specific surface area and adsorption capacity of the carbon sheet. In a preferred embodiment of the present invention, the activator selected in the activation process includes KOH or NaOH or Na2CO3 or MgCl2 or ZnCl2 or H3PO4.

[0054] The concentration of the activator directly affects the pore structure and specific surface area of ​​the carbon sheet. In order to better obtain the pore structure and specific surface area, in a preferred embodiment of the present invention, the concentration of the activator aqueous solution during the activation process is 1-6 mol / L.

[0055] In step S5, the carbon nanotubes are grown in situ on the second material by chemical vapor deposition, immersed in an aqueous solution of cerium ammonium nitrate, heated to T1, T1 is 50°C-90°C, and cooled to T2, T2 is room temperature, i.e., 20°C-25°C.

[0056] Add ammonium cerium nitrate and trimesic acid to an organic solvent in a set ratio, and stir them thoroughly with a magnetic stirrer or an ultrasonic processor until they are completely dissolved to ensure the uniformity of the solution. In a preferred embodiment of the present invention, in step S7, the temperature T3 is 20°C-90°C, and the holding time t1 is 6h-24h.

[0057] The use of chemical vapor deposition (CVD) to grow carbon nanotubes (CNTs) is an important method in the current synthesis of nanomaterials. In a preferred embodiment of the present invention, step S5 includes step S51, wherein the carbon source is evaporated at 30°C-80°C, and the gas is brought into the activated carbon sheet reaction zone loaded with Ni catalyst on the second material for carbon nanotube growth. The carbon source is a xylene solution in which the auxiliary catalyst ferrocene is dissolved, and the concentration of ferrocene in the xylene solution is 0.01g / mL-0.1g / mL. Select a suitable catalyst, such as nickel (Ni) particles, which are usually coated on the activated carbon sheet. The particle size and distribution of the catalyst are crucial to the growth of carbon nanotubes. Activated carbon is prepared by a variety of methods to ensure that its surface has good catalytic activity and high specific surface area. An inert gas (such as nitrogen or helium) is used as a carrier gas to bring the evaporated carbon source into the reaction zone. Ensure that the gas flow rate is moderate to promote effective carbon nanotube growth. After the reaction is completed, the temperature of the reactor is gradually reduced to avoid damage to the material by thermal stress. The morphology, size and structure of the produced carbon nanotubes were analyzed using scanning electron microscopy (SEM), transmission electron microscopy (TEM), Raman spectroscopy and X-ray diffraction (XRD). Figure 2-4 shown.

[0058] In a preferred embodiment of the present invention, in step S7, the organic solvent is N,N-dimethylformamide, the concentration of the aqueous solution of cerium ammonium nitrate is 0.4 mol / L-0.6 mol / L, and the mass of trimesic acid is 0.8-1.2 g. Using N,N-dimethylformamide (DMF) as an organic solvent to mix the aqueous solution of cerium ammonium nitrate and trimesic acid can more effectively promote the reaction.

[0059] In order to thoroughly rinse the material in deionized water to remove unreacted chemicals, residual catalysts and other impurities. Set the temperature of the tube furnace. Common firing temperatures range from 300°C to 1000°C, and the specific temperature depends on the desired material properties. In a preferred embodiment of the present invention, in step S8, the firing temperature in the tube furnace is 700°C-900°C, and the firing time is 1h-6h.

[0060] like Figure 4 The present invention also discloses a supercapacitor composite electrode, which is prepared by the above-mentioned method for preparing a high-load supercapacitor electrode, and comprises CeO2 / BWC-CNTs.

[0061] Example 1

[0062] The balsa wood was cut along the longitudinal direction of the tree growth to obtain balsa wood chips with a thickness of 5 mm; the balsa wood chips were heat-insulated in air protection at a temperature of 250°C for 6 hours, and then transferred to a tube furnace, carbonized in argon gas with a flow rate of 200sccm, at a carbonization temperature of 1000°C for 6 hours, and then polished with 3000 grit sandpaper to a thickness of 1 mm, cleaned with deionized water and ethanol, and then dried at 120°C for 4 hours to obtain balsa wood carbon sheets. The balsa wood carbon sheets were completely immersed in an aqueous solution containing KOH (concentration of 3 mol / L) for soaking at a temperature of 30°C for 12 hours, and then activated in argon gas (200sccm) at an activation temperature of 750°C for 2 hours, and then washed with dilute hydrochloric acid solution and deionized water to neutrality, and dried at 120°C for 4 hours. The first material is immersed in a Ni(NO3)2 solution (concentration of 0.25 mol / L) at a temperature of 30°C for 12 hours, followed by freeze drying; the carbon source (a xylene solution containing an auxiliary catalyst ferrocene, the concentration of ferrocene in xylene being 0.05 g / mL) is evaporated at 55°C, and is carried by a carrier gas (a mixed gas of 420 sccm argon and 180 sccm hydrogen) into the reaction zone of an activated carbon sheet loaded with a Ni catalyst on the second material for carbon nanotube growth, the growth temperature of the carbon nanotubes being 800°C, and the growth time being 60 minutes, to obtain BWC-CNTs. 4 g of ammonium cerium nitrate is dissolved in 6 mL of deionized water to obtain an aqueous solution of ammonium cerium nitrate at a concentration of 40 wt%. The dried BWC-CNTs are immersed in an aqueous solution of ammonium cerium nitrate, and placed in a 70°C forced drying oven for 50 minutes, then taken out, cooled to room temperature, and rinsed with deionized water, repeated 3 times, and finally placed in an oven at 70°C for 3 hours. Dissolve 0.8g of trimesic acid in 24mL of N,N-dimethylformamide, and slowly drip 12mL of 0.4mol / L cerium ammonium nitrate aqueous solution into the solution. Insert the dried BWC-CNTs vertically into the mixed solution and transfer it to a high-pressure reactor. React at 80°C for 2h. After the reactor cools down to room temperature, take out the carbon sheet and rinse it with deionized water several times, then dry it at 70°C for 3h to obtain Ce-MOF / BWC-CNTs. Then put Ce-MOF / BWC-CNTs into a tubular furnace, introduce nitrogen at a flow rate of 100sccm, keep it at 450°C for 4h, and then naturally cool it to room temperature to obtain CeO2 / BWC-CNTs.

[0063] Example 2

[0064] (1) cutting the balsa wood along the longitudinal direction of the tree growth to obtain balsa wood chips with a thickness of 3 mm;

[0065] (2) The balsa wood chips were heat-treated in air protection at a temperature of 200°C for 4 hours, and then transferred to a tube furnace for carbonization in an argon gas with a flow rate of 300 sccm at a temperature of 900°C for 4 hours, and then polished with 3000 grit sandpaper to a thickness of 1 mm, cleaned with deionized water and ethanol, and then dried at 120°C for 4 hours to obtain balsa wood carbon sheets;

[0066] (3) The balsa wood carbon sheet was immersed in an aqueous solution containing NaOH (concentration of 2 mol / L) at a temperature of 60°C for 9 h, and then activated in argon (200 sccm) at a temperature of 650°C for 3 h, and then washed with dilute hydrochloric acid solution and deionized water until neutral, and dried at 120°C for 4 h;

[0067] (4) soaking the material obtained in step (3) in a Ni(NO3)2 solution (concentration of 0.1 mol / L) at a temperature of 90°C for 6 h, followed by freeze drying;

[0068] (5) A carbon source (a xylene solution containing an auxiliary catalyst ferrocene, wherein the concentration of ferrocene in xylene is 0.02 g / mL) is evaporated at 75° C. and then carried by a carrier gas (a mixed gas of 500 sccm argon and 100 sccm hydrogen) into a reaction zone of an activated carbon sheet loaded with a Ni catalyst on the material obtained in step (4) to grow carbon nanotubes. The growth temperature of the carbon nanotubes is 700° C. and the growth time is 20 min.

[0069] (6) dissolving 4 g of ammonium cerium nitrate in 4 mL of deionized water to obtain an aqueous solution of ammonium cerium nitrate with a concentration of 50 wt %;

[0070] (7) Soaking the BWC-CNTs obtained in step (5) in the aqueous solution of ammonium cerium nitrate prepared in step (6), and placing it in a forced air drying oven at 80° C. for 60 minutes, then cooling it to room temperature and rinsing it with deionized water, repeating this process three times, and finally placing it in an oven at 70° C. and drying it for 3 hours;

[0071] (8) Dissolve 1 g of trimesic acid in 24 mL of N,N-dimethylformamide, and slowly drop 12 mL of a 0.5 mol / L aqueous solution of cerium ammonium nitrate into the solution;

[0072] (9) vertically inserting the BWC-CNTs dried in step (7) into the mixed solution in step (8), and transferring to a high-pressure reactor, reacting at 100° C. for 3 h, after the reactor is cooled to room temperature, taking out the carbon sheet, rinsing it with deionized water for several times, and then drying it at 70° C. for 3 h to obtain Ce-MOF / BWC-CNTs;

[0073] (10) The Ce-MOF / BWC-CNTs obtained in step (9) were placed in a tubular furnace, nitrogen gas was introduced at a flow rate of 100 sccm, and the mixture was kept at 550°C for 5 h and then naturally cooled to room temperature to obtain CeO2 / BWC-CNTs.

[0074] Example 3

[0075] (1) cutting the balsa wood along the longitudinal direction of the tree growth to obtain balsa wood chips with a thickness of 6 mm;

[0076] (2) The balsa wood chips were heat-treated in air protection at a temperature of 300° C. for 8 hours, and then transferred to a tube furnace for carbonization in an argon gas with a flow rate of 500 sccm at a carbonization temperature of 1100° C. for 10 hours, and then polished with 3000 grit sandpaper to a thickness of 1 mm, cleaned with deionized water and ethanol, and then dried at 120° C. for 4 hours to obtain balsa wood carbon sheets;

[0077] (3) The balsa wood carbon sheet was immersed in an aqueous solution containing ZnCl2 (concentration of 6 mol / L) at a temperature of 70°C for 20 min, and then activated in argon (200 sccm) at a temperature of 700°C for 1 h, and then washed with dilute hydrochloric acid solution and deionized water until neutral, and dried at 120°C for 4 h;

[0078] (4) soaking the material obtained in step (3) in a Ni(NO3)2 solution (concentration of 0.65 mol / L) at a temperature of 50°C for 20 h, followed by freeze drying;

[0079] (5) A carbon source (a xylene solution containing an auxiliary catalyst ferrocene, wherein the concentration of ferrocene in xylene is 0.75 g / mL) is evaporated at 45° C. and then carried by a carrier gas (a mixture of 300 sccm argon and 300 sccm hydrogen) into a reaction zone of an activated carbon sheet loaded with a Ni catalyst on the material obtained in step (4) to grow carbon nanotubes. The growth temperature of the carbon nanotubes is 850° C. and the growth time is 90 min.

[0080] (6) dissolving 6 g of ammonium cerium nitrate in 4 mL of deionized water to obtain an aqueous solution of ammonium cerium nitrate with a concentration of 60 wt %;

[0081] (7) Soaking the BWC-CNTs obtained in step (5) in the aqueous solution of ammonium cerium nitrate prepared in step (6), and placing it in a 90° C. forced air drying oven for 70 minutes, then cooling it to room temperature and rinsing it with deionized water, repeating this process three times, and finally placing it in an oven and drying it at 70° C. for 3 hours;

[0082] (8) Dissolve 1.2 g of trimesic acid in 24 mL of N,N-dimethylformamide, and slowly drop 12 mL of a 0.6 mol / L aqueous solution of cerium ammonium nitrate into the solution;

[0083] (9) vertically inserting the BWC-CNTs dried in step (7) into the mixed solution in step (8), and transferring to a high-pressure reactor, reacting at 120° C. for 4 h, after the reactor is cooled to room temperature, taking out the carbon sheet, rinsing it with deionized water for several times, and then drying it at 70° C. for 3 h to obtain Ce-MOF / BWC-CNTs;

[0084] (10) The Ce-MOF / BWC-CNTs obtained in step (9) were placed in a tubular furnace, nitrogen gas was introduced at a flow rate of 200 sccm, and the mixture was kept at 650°C for 6 h and then naturally cooled to room temperature to obtain CeO2 / BWC-CNTs.

[0085] Comparative Example 1

[0086] (1) cutting the balsa wood along the longitudinal direction of the tree growth to obtain balsa wood chips with a thickness of 6 mm;

[0087] (2) The balsa wood chips were heat-treated in air protection at a temperature of 300° C. for 8 hours, and then transferred to a tube furnace for carbonization in an argon gas with a flow rate of 500 sccm at a carbonization temperature of 1100° C. for 10 hours, and then polished with 3000 grit sandpaper to a thickness of 1 mm, cleaned with deionized water and ethanol, and then dried at 120° C. for 4 hours to obtain balsa wood carbon sheets;

[0088] (3) The balsa wood carbon sheet was placed in an aqueous solution containing ZnCl2 (concentration of 6 mol / L) (completely immersed) for immersion at a temperature of 70°C for 20 seconds, and then activated in argon (200 sccm) at a temperature of 700°C for 1 hour. The sheet was then washed with dilute hydrochloric acid solution and deionized water until neutral, and dried at 120°C for 4 hours to obtain an activated BWC.

[0089] Comparative Example 2

[0090] (1) cutting the balsa wood along the longitudinal direction of the tree growth to obtain balsa wood chips with a thickness of 6 mm;

[0091] (2) The balsa wood chips were heat-treated in air protection at a temperature of 300° C. for 8 hours, and then transferred to a tube furnace for carbonization in an argon gas with a flow rate of 500 sccm at a carbonization temperature of 1100° C. for 10 hours, and then polished with 3000 grit sandpaper to a thickness of 1 mm, cleaned with deionized water and ethanol, and then dried at 120° C. for 4 hours to obtain balsa wood carbon sheets;

[0092] (3) The balsa wood carbon sheet was immersed in an aqueous solution containing ZnCl2 (concentration of 6 mol / L) at a temperature of 70°C for 20 min, and then activated in argon (200 sccm) at a temperature of 700°C for 1 h, and then washed with dilute hydrochloric acid solution and deionized water until neutral, and dried at 120°C for 4 h;

[0093] (4) soaking the material obtained in step (3) in a Ni(NO3)2 solution (concentration of 0.65 mol / L) at a temperature of 50°C for 20 h, followed by freeze drying;

[0094] (5) The carbon source (a xylene solution containing an auxiliary catalyst ferrocene, wherein the concentration of ferrocene in xylene is 0.75 g / mL) is evaporated at 45° C. and then carried by a carrier gas (a mixed gas of 300 sccm argon and 300 sccm hydrogen) into the reaction zone of the activated carbon sheet loaded with Ni catalyst on the material obtained in step (4) to grow carbon nanotubes. The growth temperature of the carbon nanotubes is 850° C. and the growth time is 90 min to obtain BWC-CNTs.

[0095] Test Example 1

[0096] The BWC electrode in Comparative Example 1, the BWC-CNTs electrode in Comparative Example 2, and the CeO2 / BWC-CNTs electrode in Example 1 were tested using SEM. The results are as follows: Figure 2 , Figure 3 and Figure 4 shown.

[0097] The test results of the BWC electrode in Comparative Example 1 are as follows: Figure 2 As shown in the figure, most of the pores distributed on the BWC electrode have a cross-sectional size of 10-30 μm. Among these pores, there are large pores with a size of 200-300 μm. For carbon electrodes, the electron storage mechanism is based on the EDLC mechanism, and its electrochemical performance strongly depends on the surface area.

[0098] In order to further increase the specific surface area and improve the electrochemical performance, carbon nanotubes were grown in all channels of the porous carbon. Figure 3 As shown in the figure, a layer of densely interwoven carbon nanotube arrays is grown in the porous carbon sheet channels by the CVD method. The diameter of a single carbon nanotube is about 100 nanometers, which greatly reduces the pore size and increases the specific surface area of ​​the electrode. The metal catalyst particles at the end of the carbon nanotubes indicate the "tip growth" mechanism of CNT.

[0099] In order to increase the pseudocapacitive properties of the composite electrode and improve its specific capacitance, CeO2 with pseudocapacitive properties was grown again on the porous carbon composited with carbon nanotubes to obtain CeO2 / BWC-CNTs in Example 1. The detection diagram is shown in FIG. Figure 4 As shown, through hydrothermal method and high-temperature sintering, some fine crystals with a diameter of about 200-300nm are grown in the pores of the BWC-CNTs electrode. These crystals, by virtue of their own specific surface area and the reduction of space after composite, greatly increase the specific surface area of ​​the electrode.

[0100] Test Example 2

[0101] The electrochemical performance of the carbon nanotube-coupled biomass porous carbon electrode was tested using a three-electrode system on a CHI 660E electrochemical workstation. Platinum foil and commercial Hg / HgO electrodes were used as counter electrode and reference electrode, respectively, the electrolyte was 3MKOH solution, and all measurements were performed at room temperature. Cyclic voltammetry tests (CV) were performed between -1V and 0V with a scan rate of 1-20mV / s. Constant current charge / discharge tests (GCD) were measured in the potential range of -1-0V with a current density of 1-20mA / cm 2 The frequency range of the electrochemical impedance spectroscopy (EIS) test was 0.01 Hz to 100 kHz, and the AC amplitude was 10 mV. According to the GCD curve of the electrode, the area specific capacitance C of the electrode was calculated by the following equation: (areal) :

[0102]

[0103] The test results are shown in Table 1.

[0104] Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 <![CDATA[Specific capacitance (mF / cm 2 )]]> 9876 11021 10321 5812 7201 Specific capacitance retention after 10,000 cycles 106% 110% 105% 98% 166%

[0105] From the comparison in Table 1, it can be seen that the specific capacitance of each electrode in the embodiment is greater than that of the electrode in the comparative example, which proves that the electrode of the present invention has a higher specific capacitance, and the capacitance retention rate of the embodiment can still be maintained above 100% after adding the pseudocapacitive material, which also proves the extremely excellent electrochemical stability of the electrode of the present invention.

[0106] It should be noted that, for the above-mentioned method embodiments, for the sake of simplicity, they are all described as a series of action combinations, but those skilled in the art should know that the present invention is not limited by the described action sequence, because according to the present invention, certain steps can be performed in other sequences or simultaneously. Secondly, those skilled in the art should also know that the embodiments described in the specification are all preferred embodiments, and the actions and modules involved are not necessarily required by the present invention.

[0107] In the above embodiments, the description of each embodiment has its own emphasis. For parts that are not described in detail in a certain embodiment, reference can be made to the relevant descriptions of other embodiments.

[0108] In addition, each functional unit in each embodiment of the present invention may be integrated into one processing unit, or each unit may exist physically separately, or two or more units may be integrated into one unit. The above-mentioned integrated unit may be implemented in the form of hardware or in the form of software functional units.

[0109] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a high-load supercapacitor electrode, characterized in that: The method for preparing the high-load supercapacitor electrode comprises: Step S1, cutting the balsa wood along the longitudinal direction of the tree growth to obtain balsa wood chips with a thickness of d; Step S2, subjecting the balsa wood chips to a stabilization treatment process, and then to a carbonization treatment, followed by sandpaper polishing, cleaning and drying to obtain balsa wood carbon chips; Step S3, soaking the balsa wood carbon sheet in an aqueous solution containing an activator, and then activating, washing and drying to obtain a first material; Step S4, immersing the first material in a Ni(NO3)2 solution to introduce a Ni catalyst, and freeze-drying to obtain a second material; Step S5, in-situ growing carbon nanotubes on the second material by chemical vapor deposition to obtain a third material; Step S6, immersing the third material in an aqueous solution of cerium ammonium nitrate, heating the temperature to T1, cooling to T2, rinsing with deionized water, repeating 3 to 10 times, and drying to obtain a fourth material; Step S7, adding an aqueous solution of ammonium cerium nitrate and trimesic acid to an organic solvent to form a uniform solution; soaking the fourth material in the uniform solution, and placing it in a high-pressure reactor at a temperature of T3 and maintaining it for a time of t1 to obtain a fifth material; Step S8, washing the fifth material with deionized water, placing it in an oven to dry, and placing the dried material in a tubular furnace to sinter, thereby obtaining CeO2 / BWC-CNTs.

2. The method for preparing a high-load supercapacitor electrode according to claim 1, characterized in that: In step S2, the stabilization process includes heat preservation in air or argon protection, the heat preservation temperature is 200°C-300°C, and the heat preservation time is 4h-8h.

3. The method for preparing a high-load supercapacitor electrode according to claim 1, characterized in that: In step S2, the carbonization treatment is performed in an inert gas, wherein the inert gas includes argon, the carbonization temperature is 900° C.-1150° C., and the carbonization time is 4 h-12 h.

4. The method for preparing a high-load supercapacitor electrode according to claim 1, characterized in that: In step S2, the drying temperature is 110°C-120°C, and the drying time is 3h-5h.

5. The method for preparing a high-load supercapacitor electrode according to any one of claims 1 to 4, characterized in that: The activator selected in the activation process includes KOH or NaOH or Na2CO3 or MgCl2 or ZnCl2 or H3PO4, and the concentration of the activator aqueous solution in the activation process is 1-6 mol / L.

6. The method for preparing a high-load supercapacitor electrode according to claim 5, characterized in that: In step S7, the organic solvent is N,N-dimethylformamide, the concentration of the cerium ammonium nitrate aqueous solution is 0.4 mol / L-0.6 mol / L, the mass of trimesic acid is 0.8-1.2 g, the temperature T3 is 20° C.-90° C., and the holding time t1 is 6 h-24 h.

7. The method for preparing a high-load supercapacitor electrode according to claim 1, characterized in that: Step S5 includes step S51, evaporating the carbon source at 30° C.-80° C. and bringing the carbon source into the reaction zone of the activated carbon sheet loaded with Ni catalyst on the second material by gas to grow carbon nanotubes.

8. The method for preparing a high-load supercapacitor electrode according to claim 7, characterized in that: The carbon source is a xylene solution in which an auxiliary catalyst ferrocene is dissolved, and the concentration of ferrocene in the xylene solution is 0.01 g / mL-0.1 g / mL.

9. The method for preparing a high-load supercapacitor electrode according to any one of claims 6 to 8, characterized in that: In step S8, the firing temperature in the tube furnace is 700°C-900°C, and the firing time is 1h-6h.

10. A supercapacitor composite electrode, characterized in that: The supercapacitor composite electrode is prepared by the preparation method of the high-load supercapacitor electrode according to any one of claims 1 to 9, and the supercapacitor composite electrode comprises CeO2 / BWC-CNTs.

Citation Information

Patent Citations

  • Direct growth cross-linked carbon nanotubes on microstructured metal substrate for supercapacitor application

    EP4229664B1